Effects of simmering time, salt and sugar addition on the flavour and nutrient release of Morchella soup. (10th March 2023) - Fu, Ruiqing; Wang, Juan; Guo, Yanyin; Wang, Yujiang; Zhang, Haijuan
Abstract: This study aimed to investigate the effect of different simmering times, salt and sugar addition on the quality of the Morchella soup. The change in the released contents of nutrients and flavour compounds in the Morchella soup within 120 min was studied. The automatic amino acid analyser, solid‐phase microextraction–gas chromatography–mass spectrometry, phenosulphuric acid method, acid–base neutralization principle and 1, 1‐dipheny2‐picrylhydrazyl scavenging activity were used to determine the changes in free amino acids, volatile flavour compounds, total sugar, titratable acids and antioxidant activities in the Morchella soup respectively. The results showed that the amount of amino acids, volatile flavour compounds, titratable acid, antioxidant capacity and total sugar in the Morchella soup were significantly higher at 40‐min simmering time than at other simmering times. At 40‐min simmering time, the salt and sugar addition increased the amounts of umami amino acids (54.33%, 23.48%) and total amino acids (40.83%, 20.02%), organic acids (211.6%, 127.74%), sulphur‐containing compounds (130.40%, 237.20%), titratable acids (43.3%, 16.7%), and total sugar (23.8%, 16.7%) and antioxidant activity (87.5%, 23.8%) in the Morchella soup respectively. This study revealed the influence mechanism of simmering time, salt and sugar addition on the Morchella soup and provided a basis for further processing the Morchella soup. Abstract : We revealed the influence mechanism of simmering time, salt and sugar addition on the Morchella soup, found the amount of nutrient and volatile flavour compounds reached the highest level at 40‐min simmering time and salt and sugar increased the release amount of nutrient and volatile flavour compounds.